Deslizamientos en la vía Ibarra- Lita y su incidencia sobre los elementos esenciales de la parroquia la Carolina provincia de Imbabura. Periodo mayo- septiembre 2023 - Rosado Calderón, Gricelda Paulina (2023)
The present work entitled "Sliding on the Ibarra-Lita road and its impact on the essential elements of the parish La Carolina province of Imbabura. The period May-September 2023" aimed to determine the areas susceptible to landslides to establish risk reduction measures. The present research is descriptive, mixed and field type, using qualitative and quantitative methodologies, the determination of the areas susceptible to landslides was carried out by means of the methodology according to the Mohr Coulomb law, the factors of soil texture, soil density and friction angle are used, to obtain the chronic unstable characteristic of the slope, in addition to the use of the Geo5 software to check the result of the stability of the slope, at the chronic unstable point. To obtain the results of the degree of susceptibility of the essential elements, the methodology of the (UNDP; SNGR, 2011) was considered to evaluate the variables of the road system, bridges, drinking water system and the electrical system, obtaining a level between low and medium. Finally, structural and non-structural risk reduction measures were established based on the initial information of the first objective, measures and actions were also designed that must be considered by the authorities to reduce the degree of susceptibility of the essential elements.